2019
DOI: 10.1108/sampj-10-2018-0287
|View full text |Cite
|
Sign up to set email alerts
|

Help or resistance? Product market competition and water information disclosure: evidence from China

Abstract: Purpose This paper investigates the relationship between product market competition and firms’ water information disclosure and how firms’ ownership type can affect this relationship in China, offering new insights into corporate water management. Design/methodology/approach The authors investigated 303 Chinese listed companies in highly water-sensitive industries to examine how product market competition influences corporate water information disclosure by subdividing the product market competition into mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…There is also evidence of mimetic isomorphism and consideration of competitor practices (Robertson & Samy, 2015; Wijethilake et al, 2017). The influence of industry competition has been inconclusive and some scholars have argued the relationship is non‐linear (Meng et al, 2019; Zhou et al, 2020).…”
Section: Framework For Sustainability Accounting Influencesmentioning
confidence: 99%
“…There is also evidence of mimetic isomorphism and consideration of competitor practices (Robertson & Samy, 2015; Wijethilake et al, 2017). The influence of industry competition has been inconclusive and some scholars have argued the relationship is non‐linear (Meng et al, 2019; Zhou et al, 2020).…”
Section: Framework For Sustainability Accounting Influencesmentioning
confidence: 99%
“…We control some other variables to test the robustness of our results to avoid the influence of unknown factors inside and outside the enterprise on water information disclosure. First, Zhou, Zhang, Chen, Zeng and Chen (2020) showed that the intensity of industry competition influences water information disclosure. Thus, we include the Herfindahl–Hirschman Index ( HHI ) to measure the intensity of competition in the industry.…”
Section: Robustness Testsmentioning
confidence: 99%
“…Pan et al (2020) and Zhou et al (2019a) examined the impact of China’s unique political institutions on companies’ environmental performance and disclosure, enriching the understanding of companies’ environmental behaviors in transitioning countries. Zhou et al ’s (2019b) research is one of the few contemporary studies on companies’ information disclosure about water pollution. These studies uncover the role of prosecuted corrupt officials Chinese People's Political Consultative Conference (CPPCC) involved in environmental issues, which has been rarely explored in the extant literature.…”
Section: Special Issue On Chinamentioning
confidence: 99%
“…Zhou et al (2019b) explored the role of the Chinese People's Political Consultative Conference (CPPCC) in dealing with environmental challenges. The authors sampled 457 CPPCC environmental proposals across 160 cities during the period 2013 to 2015 and found that CPPCC environmental proposals helped improve environmental quality as measured by air quality in the cities.…”
Section: Special Issue On Chinamentioning
confidence: 99%